Деякі аспекти дослідження стародавніх українських цитр - Зінків, І. (Народна творчість та етнографія, 2007)
The article is dedicated to some aspects of origin of vertical medieval Ukrainian zithers. Later they became one of the prototypes of modern bandura (Ukrainian musical instrument).